The effect of biodeterioration on the mechanical properties of cement mortar (2017)
Reinforced concrete (RC) is the hybrid material most used in construction worldwide and its importance in modern engineering is paramount. Thus, to evalllate its lifecycle performance, it is important to understand the RC behavior under adverse environmental conditions. In particular this work addresses the problem of concrete deterioration over time as a result of microbial attack. In this document, there is a description of novel experimental work directed to determine the effect of microbial attack on both physical and mechanical concrete properties. Also a propo.yal to take the biodeterioration effects into account in real structural design situations is presented